ChemInform Abstract: Gallium‐Assisted Transfer Hydrogenation of Alkenes. Issue 15 (April 2015) - Michelet, Bastien; Bour, Christophe; Gandon, Vincent
Abstract Optimized reaction conditions including 1, 4‐cyclohexadiene as hydrogen source in combination with a gallium carbene complex catalyst allow hydrogenative cyclization, hydroarylation, and reduction of olefins.